Synthesis and Antimicrobial Activity of Some Heterocycles: Part-V (Biological Sciences - PJSIR, 2005)
Ortho-aminonitrile (1) was prepared from ethoxymethylenemalononitrile. 4-Allylamino-1-methyl-6- methylthiopyrazolo[3,4-d]pyrimidine (4) was prepared by an initial treatment of compound (1) with carbon disulfide in pyridine followed by methylation with methyl iodide and subsequent reaction with allylamine in acetonitrile. Ortho- aminoester (5) was prepared from ethyl (ethoxymethylene) cyanoacetate. Reaction of compound (5) with formamide yielded compound (6), which was then tosylated. All compounds were screened for their antibacterial and antifungal activities.